1998
DOI: 10.1046/j.1365-2249.1998.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

VH usage and somatic hypermutation in peripheral blood B cells of patients with rheumatoid arthritis (RA)

Abstract: SUMMARYThe human antibody repertoire has been demonstrated to have a marked V-gene-dependent bias that is conserved between individuals. In RA patients, certain heavy chain V genes (V H ) have been found to be preferentially used for encoding autoantibodies. To determine if such preferential use of V H genes in autoantibodies is associated with a general distortion of the V gene repertoire in RA patients, the V H composition of peripheral blood B cells was analysed among four RA patients and four age-and sexma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
3
7
0
Order By: Relevance
“…In particular, the gene V H 4–34 is very often used by anti-DNA antibodies [28,29] and is exclusively used by cold agglutinins [30]. In agreement with Huang and colleagues' data [13], the gene V H 3–30 was found less frequently in our RA patient than in the controls. In addition to these genes, the proportion of some other variable genes like V H 1–02, 1–18 or 4–04 also differed from the published data of normal controls and provided a distinct pattern for this patient.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In particular, the gene V H 4–34 is very often used by anti-DNA antibodies [28,29] and is exclusively used by cold agglutinins [30]. In agreement with Huang and colleagues' data [13], the gene V H 3–30 was found less frequently in our RA patient than in the controls. In addition to these genes, the proportion of some other variable genes like V H 1–02, 1–18 or 4–04 also differed from the published data of normal controls and provided a distinct pattern for this patient.…”
Section: Discussionsupporting
confidence: 89%
“…Clonal expansion is a characteristic feature of the patients with RA. B-cell clones have been found in peripheral blood [13,14] and in synovial tissue [5,14]. In the present study, we were able to detect two clones within the V H 5 family before therapy.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…After alkaline denaturation, plasmids were dot blotted onto replicate Magnacharge nylon membranes (Micron Separations, Westborough, MA) using a 96-well dot blotter (Bio-Rad, Hercules, CA) and cross-linked by UV irradiation. Membranes were hybridized to a set of oligonucleotide probes (M18, M16, M76, M8, E182, M19, and M41) that discriminate between several V H 3 genes (V3-23, V3-30/3-30.5, V3-30.3, and V3-33) as described previously (37)(38)(39)(40)(41)(42). Since Abs with HIV-1 gp120-binding activity can harbor gene products derived from either the V3-30 or the V3-30.5 locus (genes at these loci may have the same sequence) (31), we scored clones that bound probes diagnostic of either locus together as V3-30/3-30.5.…”
Section: Screening Of V H 3 Clones With Gene-specific Oligonucelotidesmentioning
confidence: 99%
“…Some of the VH genes used in these HmAbs AMA are also used in autoantibodies with other specificities in systemic lupus erythematosus and rheumatoid arthritis. [25][26][27] Although it has been reported that V H 3 and V H 4 with highly mutated CDR are used in AMA, [9][10][11] and V H 3-21, V H 3-23 are used also in both the patient-and the XenoMouse-derived AMA HmAbs, the CDRs of these AMAs are distinct. Analysis of the Ig gene repertoire used by the human-type monoclonal antibodies generated in this study showed a restricted repertoire in their CDRs.…”
Section: Discussionmentioning
confidence: 99%